Polychlorinated biphenyls (PCBs) in the British environment: Sinks, sources and temporal trends - Harrad, Stuart J.; Sewart, Andrew P.; Alcock, Ruth; Boumphrey, Ruth; Burnett, Vicky; Duarte-Davidson, Raquel; Halsall, Crispin; Sanders, Gordon; Waterhouse, Keith; Wild, Simon R.; Jones, Kevin C. (Environmental pollution (1987), 1994)
This paper estimates the present UK environmental loading of polychlorinated biphenyls (PCBs). Of the estimated ≈ 40 000 t ΣPCB sold in the UK since 1954, only an estimated 1% (400 t) are now present in the UK environment. Comparisons of estimated production and current environmental loadings of congeners 28, 52, 101, 138, 153 and 180 suggest that PCB persistence broadly increases with increasing chlorination. Those PCBs that are not now present in the UK environment are considered to have been destroyed—by natural or anthropogenic mechanisms, to be still in use, to reside in landfills or to have undergone atmospheric and/or pelagic transport from the UK. The dramatic fall in PCB levels in archived UK soils and vegetation between the mid-1960s and the present is evidence that the latter mechanism is the most important and that a significant proportion of PCBs released into the UK environment in the 1960s have subsequently undergone environmental transport away from the UK. The bulk (93·1%) of the estimated contemporary UK environmental burden of ΣPCBs is associated with soils, with the rest found in seawater (3·5%) and marine sediments (2·1%). Freshware sediments, vegetation, humans and sewage sludge combined account for 1·4% of the present burden, whilst PCB loadings in air and freshwater are insignificant. Although consideration of individual congeners does not reveal any major deviations from the relative partitioning of Σ PCBs, the importance of sinks other than soils is enhanced for individual congeners, particularly 138 and 180. In particular, around 2% of the total UK burden of congener 180 is present in humans, implying that biodata as a whole may constitute an important sink for the higher chlorinated congeners. The contemporary flux of ΣPCBs to the UK surface is estimated at 19 t yr −1, compared with an estimated annual flux to the atmosphere of 44–46 t. This implies that the major sources of PCBs to the UK atmosphere have been identified and that there is currently a net loss of these compounds from the UK. These sources are: volatilisation from soils (88·1%), leaks from large capacitors (8·5%), the production of refuse-derived fuel (RDF) (2·2%), leaks from transformers (0·6%), the recovery of contaminated scrap metal (0·5%) and volatilisation from sewage sludge-amended land (0·2%). Interestingly, whilst large excesses of estimated annual fluxes to the atmosphere over deposition fluxes for individual congeners exist for congeners 28, 52 and 101, estimates of fluxes in both directions across the soil-atmosphere interface agree closely for congeners 138, 153 and 180. This suggests that lower chlorinated congeners are more susceptible to both long-range environmental transport beyond the UK and to atmospheric degradation. Retrospective analysis of dated sediment cores, vegetation and soils indicates that environmental transport from North America and continental Europe introduced PCBs into the British environment well before the onset of their commercial production in the UK in 1954. Since that time, the input of PCBs to the UK environment has essentially reflected temporal trends in UK use. After peaking in the 1960s they declined rapidly through the 1970s following restrictions on PCB use. Recent evidence, however, is that the rate of decrease has diminished and that further significant reductions in fresh environmental input will take some time to occur. Such reductions will be especially slow for humans and other biota with long life-spans. This stems partly from cross-generational transfer from parents to offspring and also because the persistence of PCBs in biota means that present body burdens will reflect past as well as current exposure.